ATSAF - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Council for Tropical and Subtropical Agricultural Research (ATSAF) was founded in Germany in 1976 as an associationof scientists from Federal research institutes, German universities and other research institutions working in the field of...